Estudio antropológico de las estructuras cefálicas en una colección osteológica procedente de Chinchero (Perú) - Herrera Ureña, José I., (Access archaeology., 2016)
This work presents an anthropological study of crania and mandibles from the osteological collection from Chinchero (Peru), currently housed at the American Archaeological and Ethnological Museum of the Complutense University of Madrid.